Barriers to adaptation and mitigation to climate change in livestock farms of Africa, South America and Europe. [P193] - Frey, Hélène; Vayssières, Jonathan; Messad, Samir; Koslowski, Franck; Stienezen, M.W.J.; Viera, Paulo Cardoso; Poccard-Chapuis, René; Blanchard, Mélanie; Silvestri, Silvia; Jalón, Silvestre García de; Lecomte, Philippe (2015)
Livestock farming contributes to climate change but in turns it is also affected by a changing climate directly on animal performances or indirectly via feed resources availability in terms of quantity and quality. Numerous studies have analysed the diversity of barriers for farmers to adopt new technologies for climate change adaptation and mitigation. But these studies were generally conducted for specific contexts. As part of the AnimalChange European research project, this work focuses on assessing farm-scale barriers across 10 countries: Senegal, Burkina-Faso, Kenya, South Africa, Madagascar, Brazil, France, Scotland, Netherlands, and Ireland, encompassing for both low and high-input systems. A generic questionnaire was designed and applied to 175 farms addressing three themes i) general data on the farmer, his farm and its environment, ii) farmer's perception on climate change, iii) likeliness for introducing management options and barriers assessment if the option is not likely to be adopted. Based on a multiple factorial analysis, we characterised the links between barriers and farm activities, pedo-climatic conditions, market access, information access, funding, and farmer's education. This broad analysis provides an overview of technical, social and economic barriers across different regions and systems. The main barriers to adoption in the South countries are mainly represented by lack of information, funding, and education, whilst in the North, the most important barriers are access to land and labour. The results of this research could be used by policy makers to understand what poses barriers to adoption across different sites. (Resume d'auteur)
Keywords: openalex:import